Merasa Pintar, Bodoh Saja Tak Punya: Kajian Akhlak Tasawuf - Sakir, Moh.; El Syam, Robingun Suyud (Indonesian Academy of Social and Religious Research (IASRR), 2025)
This research focuses on the goal of understanding feeling smart, being stupid and not having one: a study of Sufism's morals. Using a qualitative strategy of descriptive analysis through literature study, the research results show that the Sufism perspective views the nature of knowledge as belonging to Allah, and humans have knowledge only of what He desires. Islam views Allah as the center of all knowledge. Therefore, it is not permissible for humans to feel intelligent. Research implications for knowledge seekers, practitioners and scholars regarding the importance of the process of studying science to understand the nature of knowledge, not its achievements. It is hoped that the results of this research will provide benefits for sustainable Sufism education.